Find the solution set of the system by using either the substitution or elimination method

5x-2y-5=0
3x+y-3=0


Sagot :

5x-2(-3x+3)=5
11x=5+6
x=1
[tex]Elimination\ Method; \\ 5x-2y-5\to5x-2y=5 \\ 3x+y-3\ \ \to3x+y=3 \\ \\ 5x-2y=5 \\ (-2)3x+y=3 \\ \\ 5x-2y=5 \\ -6x-2y=-6 \\ \\ \frac{-x}{-1}= \frac{-6}{-1}\to\boxed{x=6} \\ \\ Solving\ for\ y; \\ Let\ x=6 \\ \\ 5x-2y=5 \\ \\ 5(6)-2y=5 \\ \\ 30-2y=5 \\ \\ -2y=5-30 \\ \\ \frac{-2y}{-2}= \frac{-25}{-2}\to\boxed{y= \frac{25}{2}} \\ \\ Hope\ it\ Helps:) \\ Domini [/tex]